Parámetros genéticos para caracteres de crecimiento en Araucaria angustifolia (Bert.) O. Ktze = Genetic parameters for growth traits in Araucaria angustifolia - Rotundo, Cristian Andres; Schoffen, Cristian Damián; Belaber, Ector (Facultad de Ciencias Forestales, Universidad Nacional de Misiones (UNaM) y EEA Montecarlo, INTA, 2025)
Genetic parameters of growth traits were estimated at 4, 7 and 9 years old in a progeny trial of Araucaria angustifolia in Misiones, Argentina. Trivariate individual tree mixed model were used. The hi2 vary between 0.27 and 0.67 for DBH and 0.24 and 0.68 for TH, at the evaluated ages. The CVa was high for DBH (≥ 10%) and moderate for TH (< 8.04%). Age-age genetic correlations between 4 and 9 years old were 0.88 for DBH and 0.68 for TH. These results indicating that selection in early age could maximize genetic gain for DBH, however, being uncertain for TH.